Alternatives to free flap surgery for maxillofacial reconstruction: focus on the submental island flap and the pectoralis major myocutaneous flap - J. K. Meier; S. Spoerl; G. Spanier; M. Wunschel; M. J. Gottsauner; J. Schuderer; T. E. Reichert; T. Ettl (BMC, 2021)
Abstract Background Microvascular tissue transfer (MTT) has been established as the gold standard in oral- and maxillofacial reconstruction. However, free flap surgery may be critical in multimorbid elderly patients and after surgery or radiotherapy, which aggravate microsurgery. This study evaluates indications and outcome of the submental island flap (SMIF) and the pectoralis major myocutaneous flap (PMMF) as alternatives to the free radial forearm flap (RFF). Methods This retrospective study included 134 patients who had undergone resection and reconstruction with SMIF, PMMF, or RFF at our department between 2005 and 2020. The level of comorbidity was measured with the Age-adjusted Charlson comorbidity index (ACCI). Primary outcome variables were flap success, complications, wound dehiscence, surgery duration, as well as time at the ICU and the ward (hospitalization). Chi-square tests, t-tests, and ANOVA were performed for statistics. Results 24 SMIFs, 52 RFFs, and 58 PMMFs were included in this study. The flap types did not significantly differ in terms of flap success, complications, and healing disorders. The SMIF presented a success rate of 95.8% and was significantly more often used in elderly patients (mean age = 70.2 years; p < 0.001) with increased comorbidities than the PMMF (p < 0.01) and RFF (p < 0.001). SMIF reconstruction reduced surgery duration (p < 0.001) and time at the ICU (p = 0.009) and the ward (p < 0.001) more than PMMF and RFF reconstructions. PMMF reconstruction was successful in 91.4% of patients and was more frequently used after head and neck surgery (p < 0.001) and radiotherapy (p < 0.001) than SMIF and RFF reconstructions. Patients undergoing PMMF reconstruction more frequently required segmental jaw resection and had presented with advanced tumor stages (both p < 0.001). Nicotine and alcohol abuse was more frequent in the RFF and PMMF groups (both p < 0.001) than in the SMIF group. Conclusions The pedicled SMIF represents a valuable reconstructive option for elderly patients with increased comorbidity because of the shorter duration of surgery and hospitalization. On the other hand, the PMMF serves as a solid backup solution after head and neck surgery or radiotherapy. The rates of flap success, complications, and healing disorders of both pedicled flaps are comparable to those of free flap reconstruction.